Development of a CubeSat Single Channel LoRa Receiver Module for Space-based IoT Application - Muhammad Dzaky Ivansyah; Edwar Edwar; Nachwan Mufti Adriansyah; Harfan Hian Ryanu; Dhoni Putra Setiawan (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
CubeSat attracts many researchers due to its low production and deployment cost. One of the application is implemented in low data rate communication or machine to machine (M2M) with IoT devices in remote areas such as islands, forests, and mountains. In this study, a CubeSat receiver for IoT communication in remote areas has been developed and realized. A LoRa SX1276 chip is used for processing passband signals captured by the antenna. The device has a amplifier gain of 20.92 dB, 390 mW power consumption, and operating frequency of 923 MHz. The developed CubeSat is expected to provide a low bit rate of 5468.750 bps for SF 7 and 292.969 for SF 12 , the receiver serves as a concentrator for monitoring devices in rural areas.